STRATEGI MENINGKATKAN PRODUKSI LELE MUTIARA (Clarias gariepinus) MELALUI TEKNOLOGI PEMIJAHAN BUATAN - Asiah, Nur; Riauwaty, Morina; Heltonika, Benny; Siagian, Desi Rahmadani; Elfina, Yetti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Air Terbit Village has a fisheries business unit known as Pembinaan Ikan Lele Mang Tata, which focuses on producing catfish seeds. This business unit applies a natural method in spawning Mutiara catfish to obtain seeds. One of the obstacles faced by this business unit is the lack of seed production. This is due to the use of natural spawning methods, traditional management, and suboptimal marketing. To increase seed production, it is necessary to identify quality broodstock and apply artificial spawning technology using funnel media. Community service activities aim to introduce artificial catfish spawning technology using funnel media to increase seed production and help overcome the challenges faced by farmers.